ChemInform Abstract: Assisted Tandem Catalysis: Metathesis Followed by Asymmetric Hydrogenation from a Single Ruthenium Source. Issue 46 (November 2015) - Renom‐Carrasco, Marc; Gajewski, Piotr; Pignataro, Luca; de Vries, Johannes G.; Piarulli, Umberto; Gennari, Cesare; Lefort, Laurent
Abstract Prochiral olefins generated by metathesis are highly enantioselectively hydrogenated by an in situ obtained chiral ruthenium catalyst.